ASSESSING POSYANDU CADRES’ READINESS IN IMPLEMENTING INTEGRATED PRIMARY HEALTH SERVICES IN YOGYAKARTA, INDONESIA - Siswati, Tri; Olfah, Yustiana; Attawet, Jutharat; Nurhidayat, Nurhidayat; Waris, Lukman (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: The readiness of Posyandu (a community-based health service) cadres’ to implement the Integrated Primary Health Services (Integrasi Layanan Primer/ILP) is vital to advancing preventive and promotive care. Aims: This study aims to evaluate the cadres’ readiness, identify challenges, and propose effective strategies for sustainable implementation. Methods: A mixed-method design from April to June 2024. 113 cadres from Kulon Progo, Sleman, and Yogyakarta City participated in a cross-sectional study. Cadres' readiness was evaluated based on the posyandu cadres’ basic skills training curriculum. Ten informants were interviewed to explore the opportunities, needs, and limitations of the ILP implementation. Descriptive statistics were used for data analysis. Results: Most cadres (63.7%) were aged 41–50 years, 60.2% had completed senior high school, and 72.6% were housewives. The cadres demonstrated high readiness for ILP implementation, with the main needs in the form of improving logistics, funding, training, and community participation. In addition, there was a need to improve the literacy and skills of cadres in providing health services across the life stages, such as immunization, growth and development monitoring, and infant and child feeding. Conclusion: Posyandu cadres are ready to implement the ILP; however, strengthening cadres’ capacity and fostering community collaboration are key strategies for ensuring the sustainability of the program and achieving health transformation. Keywords: cadres, health transformation, integrated primary service, posyandu